Does Mindfulness and Psychological Capital affect Work Engagement of Healthcare Workers? A study case in DKI Jakarta - Puspita, Putu Ayu; Syaebani, Muhammad Irfan (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: This study presents the condition of work engagement among health workers in DKI Jakarta in doing their jobs. Complaints are addressed to health workers for the lack of services provided at healthcare facilities in DKI Jakarta. This study will discuss several variables that affect the work engagement of health workers. This study will discuss several variables that affect the work engagement of health workers. This paper uses empirical methods to see the influence of mindfulness to health worker’s engagement using psychological capital as a mediator for health workers. Subjects and method: Health workers in DKI Jakarta participated in the study (N=280). The data were analyzed using structural equation modelling. Results: The results show that mindfulness is fully mediated by psychological capital. The findings can be used to increase their work engagement by exploring more deeply the use of psychological capital, and mindfulness and ultimately increasing the engagement of health workers themselves and the services provided. Conclusion: This study found a connection between mindfulness and work engagement through psychological capital and not directly from mindfulness to work engagement. This means that psychological capital is important in building a good engagement. Positive psychological capital can lead health workers to contribute more and be more engaged in their work. Keyword: mindfulness, psychological capital, work engagement, health workers